Discovery Learning with a Teaching at Right Level Approach Improves Civics Learning Outcomes of Fourth Grade Elementary School Students - Widnyani, Ni Nengah Ari; Riastini, Putu Nanci (Journal for Lesson and Learning Studies, 2024)
Learning outcomes in Civics subjects for elementary school students are still low. This is because teachers do not use learning models that suit students' learning styles. So this research aims to analyze the influence of Discovery learning using the Teaching at Right Level (TaRL) approach on Class IV Civics Learning Outcomes. The method used in this research is quantitative using a Quasi Experimental Design approach. The population in this study was all class IV consisting of class IV A and class IV B. The sample for this research was class IV A students totalling 23 students as the experimental class and class IV B students totalling 23 students as the control class. Samples were taken using a saturated sampling technique where the entire population was used as a sample. The data collection technique used is a multiple-choice test. The research data were analyzed using descriptive statistical analysis techniques and inferential statistical analysis techniques (t-test) with a significance level of 5%. The results of the research state that H1 is accepted and H0 is rejected, so it can be concluded that there is a significant influence of Discovery learning using the TaRL approach on class IV Civics learning outcomes. The implications of this research are expected to be able to make students active in learning.